The tree of life : a book depicting the life of Charles Darwin, naturalist, geologist & thinker - Sís, Peter, 1949- (New York : Farrar Straus Giroux, 2003)
Presents the life of the famous nineteenth-century naturalist using text from Darwin's writings and detailed drawings by Sis.
"Frances Foster books.".
Horn Book Starred.
School Library Journal starred.
Wilson's Children.
5.6
3-6
Keywords: Darwin, Charles, -- 1809-1882 -- Juvenile literature; Darwin, Charles, -- 1809-1882.; Darwin, Charles, -- 1809-1882.; Naturalists -- Biography -- Juvenile literature; Naturalists; Naturalists -- Biography